Climate change expected to improve digestive rate and trigger range expansion in outbreaking locusts. Issue 1 (28th September 2022) - Youngblood, Jacob P.; Cease, Arianne J.; Talal, Stav; Copa, Fernando; Medina, Hector E.; Rojas, Julio E.; Trumper, Eduardo V.; Angilletta, Michael J.; Harrison, Jon F.
Abstract: Global climate change will probably exacerbate crop losses from insect pests, reducing agricultural production, and threatening food security. To predict where crop losses will occur, scientists have mainly used correlative models of species' distributions, but such models are unreliable when extrapolated to future environments. To minimize extrapolation, we developed mechanistic and hybrid models that explicitly capture range‐limiting processes, and we explored how incorporating mechanisms altered the projected impacts of climate change for an agricultural pest, the South American locust ( Schistocerca cancellata ). Because locusts are generalist herbivores surrounded by food, their population growth may be limited by thermal effects on digestion more than food availability. To incorporate this mechanism into a distribution model, we measured the thermal effects on the consumption and defecation of field‐captured locusts and used these data to model energy gain in current and future climates. We then created hybrid models by using outputs of the mechanistic model as predictor variables in correlative models, estimating the potential distribution of gregarious outbreaking locusts based on multiple predictor sets, modeling algorithms, and climate scenarios. Based on the mechanistic model, locusts can assimilate relatively high amounts of energy throughout temperate and tropical South America; however, correlative and hybrid modeling revealed that most tropical areas are unsuitable for locusts. When estimating current distributions, the top‐ranked model was always the one fit with mechanistic predictors (i.e., the hybrid model). When projected to future climates, top‐ranked hybrid models projected range expansions that were 23%–30% points smaller than those projected by correlative models. Therefore, a combination of the correlative and mechanistic approaches bracketed the potential outcomes of climate change and enhanced confidence where model projections agreed. Because all models projected a poleward range expansion under climate change, agriculturists should consider enhanced monitoring and the management of locusts near the southern margin of the range.